2023
DOI: 10.1002/cncr.34665
|View full text |Cite
|
Sign up to set email alerts
|

Genomic and proteomic characterization of Philadelphia‐like B‐lineage acute lymphoblastic leukemia: A report of Indian patients

Abstract: Background The gold standard for the identification of Philadelphia (Ph)‐like acute lymphoblastic leukemia (ALL) patients is gene expression profiling. Because of its diverse nature, its identification is extremely difficult and expensive. On the genomic and proteomic landscape of Ph‐like ALL patients, there is a paucity of published literature from developing countries. Methods The authors used digital barcoded nCounter NanoString gene expression profiling for its detection, followed by molecular and proteomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 56 publications
0
7
0
Order By: Relevance
“…In the present study, we observed a higher frequency of 18% BCR::ABL1 fusion, followed by 4.9% ETV6::RUNX1 fusion, 3.8% TCF3::PBX1 fusion, 1.2% KMT2A::AFF1 fusion, and 26.67% BCR::ABL1 ‐like ALLs of all B‐ALL patients. The authors from high‐income and low‐income countries reported the recurrent genetic abnormalities (RGA) frequencies including 0.6%–35% BCR::ABL1 ‐positive ALLs, 0.8%–30.6% ETV6::RUNX1 , 0.8%–6.2% TCF3::PBX1 , 0.5%–19% KMT2A‐AFF1 , and 10%–33.1% BCR::ABL1 ‐like ALL cases 6,7,12‐15,17,18,20,28,31,32,34,37,41,49‐61 . The overall frequencies of RGAs and BCR::ABL1 ‐like ALL cases reported in the literature from low‐income and high‐income countries among B‐ALL patients (from India as well as other countries) are summarized in Table 3.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, we observed a higher frequency of 18% BCR::ABL1 fusion, followed by 4.9% ETV6::RUNX1 fusion, 3.8% TCF3::PBX1 fusion, 1.2% KMT2A::AFF1 fusion, and 26.67% BCR::ABL1 ‐like ALLs of all B‐ALL patients. The authors from high‐income and low‐income countries reported the recurrent genetic abnormalities (RGA) frequencies including 0.6%–35% BCR::ABL1 ‐positive ALLs, 0.8%–30.6% ETV6::RUNX1 , 0.8%–6.2% TCF3::PBX1 , 0.5%–19% KMT2A‐AFF1 , and 10%–33.1% BCR::ABL1 ‐like ALL cases 6,7,12‐15,17,18,20,28,31,32,34,37,41,49‐61 . The overall frequencies of RGAs and BCR::ABL1 ‐like ALL cases reported in the literature from low‐income and high‐income countries among B‐ALL patients (from India as well as other countries) are summarized in Table 3.…”
Section: Discussionmentioning
confidence: 99%
“…ABL1-positive ALLs, 0.8%-30.6% ETV6::RUNX1, 0.8%-6.2% TCF3:: PBX1, 0.5%-19% KMT2A-AFF1, and 10%-33.1% BCR::ABL1-like ALL cases. 6,7,[12][13][14][15]17,18,20,28,31,32,34,37,41,[49][50][51][52][53][54][55][56][57][58][59][60][61] monoclonal antibody clone type, and differences in flow cytometry methodology, processing, and data analysis. 74,76 Table 4 compares the reported frequencies of myeloid marker expression in B-ALL patients.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, in lymphoblastic leukemia's, when the cells involved are B and T lymphocytes, when they are transformed, called lymphoblast's, and myeloid progenitor cells, such as granulocytes and monocytes, are involved. Gupta, D. G.,et al [34] has discussed another important classification concerns acute leukemia, which occurs more often in children and adolescents and is usually more aggressive and fast-moving and chronic forms, which mainly affect people in their 40s and 50s. Sekar, G.,et al [35] has discussed an environmental factors, including exposure to ionizing radiation following or connected to diagnostic or therapeutic procedures, for example, associated with environmental pollution, for example, the famous case of the explosion at the Chernobyl nuclear power plant or chemical carcinogens, including benzene, benzopyrene, toxic aldehydes and some heavy metals.…”
Section: A Analysis Based On Diagnosismentioning
confidence: 99%
“…Chemotherapy is the primary treatment. However, depending on your subtype, you may receive alternative treatment Guo, M.,et al [33] In lymphoblastic leukemia's, when the cells involved are B and T lymphocytes, when they are transformed, called lymphoblast's, and myeloid progenitor cells Gupta, D. G.,et al [34] This disease occurs more often in children and adolescents and is usually more aggressive and fast-moving and chronic forms, which mainly affect people in their 40s and 50s…”
Section: Authorsmentioning
confidence: 99%
“…BCR::ABL1 ‐like/Ph‐like ALL has been incorporated as a provisional entity in the World Health Organization classification 2016, and it is considered an entity in the revised World Health Organization 2022 classification of the hematolymphoid neoplasms 10,11 . Ph‐like ALL cases share the same gene expression profile (GEP) as Ph‐positive ALL without expressing BCR::ABL1 fusion transcripts originating from Ph chromosome 1,6,8,12–43 . The peak incidence of Ph‐like ALL cases is in adolescents and young adults up to 33.1%, whereas it decreases with advancing age.…”
Section: Introductionmentioning
confidence: 99%